2006
DOI: 10.1002/jnr.20889
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide donor molsidomine attenuates psychotomimetic effects of the NMDA receptor antagonist MK-801

Abstract: There is experimental evidence indicating that the non-competitive NMDA receptor antagonist MK-801 impairs cognition and produces a series of schizophrenia-like symptoms in rodents (hypermotility, stereotypies, and ataxia). The present study was designed to investigate the efficacy of the nitric oxide (NO) donor molsidomine in counteracting these MK-801-induced behavioral effects in the rat. In a first study, post-training administration of molsidomine (at 4 but not 2 mg/kg) successfully antagonized MK-801-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
2
14
0
1
Order By: Relevance
“…Our study results are in line with previous studies in which post-training administration of both MK-801 and ketamine disrupted rats' performance in the novel object recognition task (Pitsikas et al, 2006(Pitsikas et al, , 2008. A single post-training injection of L-NAME (1 and 3, but not 10 mg/kg) attenuated either the MK-801-or the ketamine-induced performance deficits in this recognition memory paradigm.…”
Section: Novel Object Recognition Tasksupporting
confidence: 82%
See 2 more Smart Citations
“…Our study results are in line with previous studies in which post-training administration of both MK-801 and ketamine disrupted rats' performance in the novel object recognition task (Pitsikas et al, 2006(Pitsikas et al, , 2008. A single post-training injection of L-NAME (1 and 3, but not 10 mg/kg) attenuated either the MK-801-or the ketamine-induced performance deficits in this recognition memory paradigm.…”
Section: Novel Object Recognition Tasksupporting
confidence: 82%
“…Doses of L-NAME were chosen on the basis of a study in which they were effective against learning impairments and did not produce adverse side effects (Boultadakis et al, 2010). The doses of MK-801 (0.1 mg/kg) and ketamine (3 mg/kg) were selected based on previous findings in which they were found to impair rat performance in the novel object recognition task without producing side effects (Pitsikas et al, 2006(Pitsikas et al, , 2008. For the radial water maze test, the dose of ketamine (15 mg/kg) was chosen based on a previous report in which it was found to impair place learning in a water maze task (Wesierska et al, 1990).…”
Section: Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that N-methyl D-aspartate NMDA receptor antagonists result into stereotypic movement disorder (32,33), while sulindac increases the NR1 and NR2B NMDA receptor subunits in aged Fischer 344 rats (34). NMDA receptors are vital for brain function and these receptors are central to many of the activity-dependent changes occurring in synaptic strength and connectivity (35).…”
Section: Discussionmentioning
confidence: 99%
“…In view of its importance in recognition memory, hippocampus was targeted to receive CART, CART-antibody, or U0126. MK-801 was administered via the peripheral routes; this route is widely used to produce memory impairment (Pitsikas et al, 2006(Pitsikas et al, , 2008van der Staay et al, 2011;Reneerkens et al, 2013). Fifteen (icv or ih) or 30-min (ip) following injection, individual rats were exposed to a familiarization trial with two identical objects in the arena for 5-min.…”
Section: Drug Preparation and Administrationmentioning
confidence: 99%